CORRELATION BETWEEN THE ABUDANCE OF CHEMICAL ELEMENTS AND THE NUMBER OF THEIR MINERALS IN THE CONTINENTAL CRUST - Ivanov V.V.; Yushko-Zakharova O.Y. (My University, 1989)
The question regarding the influence of the abundance of a chemical element on the total number of its mineral species has attracted the attention of researchers. At the present time, more complete statistical data on the number of mineral species is available. This allows one to make this relationship more precise, based on Vernadskiy's geochemical classification of chemical elements by decades. This classification groups together chemical elements which are similar in abundance in the Earth's crust. This parameter, which takes into account the fact that fundamental mineralogical and geochemical regularities are governed by the law of mass action, is the most suitable for elucidating the problem which interests us.